2013
DOI: 10.1161/circulationaha.112.000045
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Preconditioning Attenuates Myocardial Ischemia/Reperfusion Injury via Caveolin-3–Dependent Cyclooxygenase-2 Inhibition

Abstract: Background The inhaled anesthetic sevoflurane has been demonstrated to protect against myocardial ischemia/reperfusion (MI/R) injury, via mechanisms involving AMP-activated protein kinase (AMPK) and caveolin-3 (Cav-3). However, the relative contributions of AMPK and Cav-3 to sevoflurane preconditioning-mediated cardioprotection, and their precise underlying mechanisms of action, remain incompletely understood. Methods and Results Sevoflurane preconditioning (SF-PreCon, consisting of 3 cycles of 15 minute-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…Within these microdomains, caveolins (Cav) are structural proteins of caveolae [12, 13], which interact with numerous signaling molecules (such as eNOS, PI3K, and MER/MRK etc.) that are required in cardiac protection initiated by a variety of cardioprotective interventions (e.g., ischemic preconditioning [14] and anesthetic preconditioning [15]). Cardiac I/R tolerance parallels the expression of Cav-3, the cardiac-specific isoform of Cav.…”
Section: Introductionmentioning
confidence: 99%
“…Within these microdomains, caveolins (Cav) are structural proteins of caveolae [12, 13], which interact with numerous signaling molecules (such as eNOS, PI3K, and MER/MRK etc.) that are required in cardiac protection initiated by a variety of cardioprotective interventions (e.g., ischemic preconditioning [14] and anesthetic preconditioning [15]). Cardiac I/R tolerance parallels the expression of Cav-3, the cardiac-specific isoform of Cav.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its dysregulation is involved in the development of arrhythmia, myocardial hypertrophy, and myocardial ischemia/reperfusion injury [17-19]. However, no previous studies elucidated the regulatory role of Cav3 during the development of cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cav3 is involved in signal transduction both inside and outside of the myocardial cell membrane, and its defects are closely associated with heart disease development. Previous studies reported that Cav3 contributes to a variety of cardiac pathophysiological processes such as arrhythmogenesis, myocardial hypertrophy, and myocardial ischemia/reperfusion injury [17-19]. Cav3 was shown to be associated with protein kinase C (PKC) signaling, known to induce fibrogenesis [20-22].…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled anesthetics (including sevoflurane) reduce myocardial injury and the need for inotropic support in cardiac patients (Zhao et al, 2013). Our meta-analysis explored the role of inflammatory cytokines, IL-6 and IL-8, in groups pretreated and post-treated with sevoflurane.…”
Section: Discussionmentioning
confidence: 99%